THE IMPORTANCE OF SHAPE IN LEARNING NEW WORDS (Universal International Scientific Journal, 2026)
This article analyzes the phenomenon of the shape bias in young children’s wordacquisition. In particular, it highlights that when generalizing novel nouns, children tend to rely moreon an object’s shape than on its other properties, treating shape as the primary feature for categorization.The paper reviews and analyzes studies that have provided empirical support for this approach,discussing how the shape bias varies depending on age and object type (animate vs. inanimate; solid vs.non-solid). In addition, evidence is presented showing that children attend not only to shape similaritybut also to other object properties. The article concludes that word acquisition is influenced not only byperceptual factors but also by cognitive and conceptual processes.
Keywords: language development; vocabulary acquisition; form preference